Anatomical and radiographic study on the appendicular skeleton of the Tamandua mexicana - Calvo Varela, Ariana (2022)
Tamandua mexicana species has an important role in the natural ecosystem as a pest controller, feeding on insects such as termites. One of the main anatomical adaptations that this species has undergone has been to its thoracic extremities. Having detailed knowledge regarding the osteology of the thoracic limbs of T. mexicana provides a strong base for its application in clinical-surgical practice. In addition to collaborating with the greater understanding of animal physiology and behavior. Because there was a lack of description about the appendicular skeleton anatomy of this species, the objective of this investigation was to describe the osteology and the radiographic anatomy of the appendicular skeleton of the T. mexicana. The bones used belonging to the appendicular skeleton of two specimens of T. mexicana were properly cleaned using standard boiling and maceration techniques. The morphometry of the bones was performed using a measuring tape, pachymeter, and radiographies. With this study, it was possible to identify and describe the anatomical peculiarities such as the presence of the double scapular spine that shapes the caudolateral fossa, and at the end of the humerus, the supratrochlear foramen, in addition to a markedly prominent medial epicondyle. In addition, a difference was observed between metacarpal bones and the phalanges of the third digit compared to the other ones, as it is significantly thicker. These findings reinforced the evidence that a certain degree of anatomical specialization is a result of an adaptation of this species to its environment and diet. The knowledge provided by research like this contributes to the improvement of surgical techniques and diagnostic approach in the species.